Evaluasi Pelatihan Keselamatan terhadap Kesadaran K3 dan Tanggung Jawab Kerja Berdasarkan Etika Kerja Islam di Perusahaan Logistik - Zahara, Shafira; Gustiningsih, Firanda; Putri, Nur Afifah Dwi Laksana; Hasanah, Ummatul; Maududi, Abul A'la Al (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Safety training is a strategic effort in building an Occupational Safety and Health (OHS) culture in the logistics industry, which has a high risk of accidents. This study aims to evaluate the effectiveness of safety training in increasing employee OHS awareness and work responsibilities by considering Islamic work ethics values. The study used a descriptive qualitative method with an evaluative approach based on the CIPP (Context, Input, Process, Product) model. Data were collected through in-depth interviews with 10 informants consisting of OHS managers, supervisors, and operational employees at logistics company “X” in Jakarta, as well as observations and documentation studies of training modules. Data analysis was conducted using thematic techniques. The results of the study indicate that safety training has been running well from the context and input aspects, but at the process and product stages there are still obstacles in the continuous evaluation and internalization of Islamic work ethics values. Values ​​such as amanah, discipline, and ihsan have been shown to strengthen employee awareness and work responsibilities after training. This study concludes that safety training integrated with Islamic work ethics can improve the effectiveness of OHS implementation and strengthen work morale in the logistics sector.